PUBLIC DIPLOMACY OF INDONESIAN FILM AGENCY THROUGH FILM INDUSTRY AS INTERNATIONAL POLITICAL INSTRUMENTS - Ali Zahid Habibullah; Chandra Purnama; Teuku Rezasyah (JWP (Jurnal Wacana Politik), 2022)
Public diplomacy is one of the instruments commonly used in international political activities. More precisely, public diplomacy discusses diplomatic activities carried out by state and non-state actors towards foreign publics in order to fulfill the interests of the relevant state. Various instruments can be used in public diplomacy activities such as books, television programs, brands, festivals, products, and films. In fact, information obtained by the public regarding a country comes from non-government actors. If uncontrolled, information circulating, especially from non-government actors, can cause problems for the national interest of a country. The problem is related to the influence of information on the image of the country in question. As stated by Leonard (2002) that the ideal public diplomacy activity can be formed if there is a synergistic effort between government and non-government actors. This study seeks to discuss public diplomacy activities that use the film industry as an instrument. The actor chosen as the main object in this research is the Indonesian Film Agency (BPI). This study will use the theory of public diplomacy developed by Mark Leonard with descriptive qualitative research methods. The data collection method used in this research is through interviews and literature studies through various sources, both primary and secondary. In general, this research will provide an overview of the understanding of Mark Leonard’s theory of public diplomacy based on what has been done by BPI. In the end, this understanding will show the gap between theory and reality regarding Indonesian public diplomacy activities that use the film industry as an instrument. When referring to Leonard’s theory of public diplomacy, BPI has the potential to produce an ideal public diplomacy effort. Therefore, efforts to build a more integrated relationship between BPI and the Indonesian government are deemed necessary in order to maximize the role of BPI as both an actor in public diplomacy.